Somatic DNA Damage Response and Homologous Repair Gene Alterations and Its Association With Tumor Variant Burden in Breast Cancer Patients With Occupational Exposure to Pesticides - Scandolara, Thalita Basso; Valle, Sara Ferreira; Esteves, Cristiane; Scherer, Nicole de Miranda; de Armas, Elvismary Molina; Furtado, Carolina; Gomes, Renan; Boroni, Mariana; Jaques, Hellen dos Santos; Alves, Fernanda Mara; Rech, Daniel; Panis, Carolina; et al. (Frontiers in Oncology, 2022)
Homologous recombination is a crucial pathway specialized in repairing double-strand breaks, thus, alterations in genes of this pathway may lead to loss of genomic stability and cell growth suppression. Pesticide exposure potentially increases cancer risk through several mechanisms, such as the genotoxicity caused by chronic exposure, leading to gene alteration. To analyze this hypothesis, we investigated if breast cancer patients exposed to pesticides present a different mutational pattern in genes related to homologous recombination (BRCA1, BRCA2, PALB2 and RAD51D) and damage-response (TP53), concerning unexposed patients. We performed multiplex PCR-based assays and NGS sequencing of all coding regions and flanking splicing sites of BRCA1, BRCA2, PALB2, TP53, and RAD51D in 158 unpaired tumor samples from breast cancer patients on MiSeq (Illumina) platform. We found that exposed patients had tumors with more pathogenic and likely pathogenic variants than unexposed patients (p=0.017). In general, tumors that harbored a pathogenic or likely pathogenic variant had a higher mutational burden (p<0.001). We also observed that breast cancer patients exposed to pesticides had a higher mutational burden when diagnosed before 50 years old (p=0.00978) and/or when carrying BRCA1 (p=0.0138), BRCA2 (p=0.0366), and/or PALB2 (p=0.00058) variants, a result not found in the unexposed group. Our results show that pesticide exposure impacts the tumor mutational landscape and could be associated with the carcinogenesis process, therapy-response, and disease progression. Further studies should increase the observation period in exposed patients to better evaluate the impact of these findings.